Effects of some antibiotic residues on some health parameters of two species of fish in Shatt Al-Arab, southern Iraq - Ahmed, Mayada (Iraqi Journal of Aquaculture, 2026)
The presence of antibiotics in the aquatic environment poses great concerns because of their impacts on water quality, aquatic organisms and human health. This study aimed to detect the residues of antibiotics including (Amoxicillin (AMO), Ciprofloxacin (CIP) and Levofloxacin (LEV)) seasonally in the muscles and liver of (Planiliza abu) and (Oreochromis niloticus) fish and indicating their effects on some health aspects of fish during November 2020 to August 2021 in two selected stations from Shatt Al-Arab, Basrah, Iraq. The samples were analysed using high performance liquid chromatography (HPLC). The study recorded high levels of antibiotics in the muscles and liver of fish, and the concentrations were higher in the second station than in the first one. In P. abu the antibiotic AMO occupied the highest concentration in the muscles and liver of fish in the second station during the spring exhibiting )8.7 and 6.2 mg kg-1(, respectively. The lowest values of CIP were recorded in fish muscles in the first station during the autumn, amounting to (2.8 mg kg-1). The lowest values of LEV were recorded in fish livers in the first station during the autumn amounting to (1.3 mg kg-1). While in O. niloticus fish the antibiotic CIP had the highest concentration (7.4 mg kg-1) in muscles in the spring, and the AMO showed the highest concentration (4.1 mg kg-1) in the liver during the spring. In this study, the accumulation of antibiotics in the liver and muscles of fish exhibited negative effects on the health standards. The presence of antibiotic residues in fish samples in these high concentrations is a source of great concern as it is a major source of human food. The study emphasized the need to conduct more studies to detect this type of pollution and know its negative effects on the health aspects of other types of fish.